A functional high-temperature thermal protective coating with intrinsic low thermal conductivity and high emissivity

By using high-temperature thermal protective coatings prepared from high-entropy rare earth perovskite materials, the problem of poor thermal conductivity and infrared emissivity of existing coatings in high-temperature environments is solved, and the effects of low thermal conductivity and high infrared emissivity are achieved, and Improved coating stability and adhesion.

CN118146660BActive Publication Date: 2025-01-21LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410271599.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-11
Publication Date
2025-01-21
Estimated Expiration
2044-03-11

AI Technical Summary

Technical Problem

Existing high-temperature thermal protection coatings are difficult to meet modern industrial needs in high temperature, high pressure and complex environments, especially in terms of thermal conductivity and infrared emissivity, and have problems with stability and adhesion.

Method used

High-entropy rare earth perovskites are used as functional pigments, and high-temperature thermal protective coatings with intrinsically low thermal conductivity and high emissivity are prepared through processes such as ball milling mixing and high-temperature calcination. The coating is composed of functional pigments, fillers, high-temperature binders, additives and deionized water. Through specific proportions and processes, the infrared radiation rate and structural stability of the coating are improved.

Benefits of technology

It achieves low thermal conductivity and high infrared emissivity of the coating in high-temperature environments, improves the structural stability and high-temperature corrosion resistance of the coating, reduces the attenuation rate of infrared radiation performance, and has strong coating adhesion without blistering or turtles. crack.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118146660B_ABST
    Figure CN118146660B_ABST
Patent Text Reader

Abstract

The present invention relates to a functional high-temperature thermal protective coating with intrinsic low thermal conductivity and high emissivity. The working temperature of the high-temperature thermal protective coating is 800-1500°C and the thermal conductivity is 1.2-1.6Wm ‑1 K ‑1 , composed of the following raw materials in parts by weight; 10-15 parts of functional pigment, 20-25 parts of filler, 20-30 parts of high-temperature binder, 3-8 parts of auxiliary agent and 15-25 parts of deionized water; the functional pigment is a high-entropy rare earth perovskite, and the chemical formula is RECrO3, wherein RE is five of the rare earth elements La, Pr, Ce, Nd, Sm, Gd, Y, and Dy, and each rare earth element is in an equimolar ratio. The present invention has good infrared radiation characteristics and low thermal conductivity, and the coating has excellent adhesion, thermal shock resistance and corrosion resistance. The coating prepared by the coating of the present invention can fully balance the heat exchange ratio of the heating surface of the high-temperature device, strengthen the radiation heat exchange capacity, which is mainly manifested in reducing the heat accumulation on the aviation and aerospace surfaces and increasing the service life; enhancing the thermal utilization rate of high-temperature processing kilns, and playing a role in energy saving and efficiency improvement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of high-temperature thermal protection, and in particular to a functional high-temperature thermal protection coating with intrinsic low thermal conductivity and high emissivity. Background Art

[0002] With the rapid development of modern science and technology and industry, especially in the fields of aviation, aerospace, nuclear energy and high temperature processing, the demand for thermal protection of materials and equipment in high temperature environments is increasing. Traditional high temperature thermal protection materials often cannot meet the needs of modern industrial applications, especially in high temperature, high pressure and complex environments.

[0003] High-temperature thermal protective coatings are materials used to protect substrates in high-temperature environments. Traditional high-temperature thermal protective coatings mainly rely on the physical thermal insulation function of the coating, and improve the thermal insulation effect by increasing the thickness of the coating or changing its composition. However, these methods often bring about problems such as increased coating weight, decreased adhesion, and unstable heat resistance. In recent years, some researchers have begun to explore the use of the intrinsic properties of materials to achieve efficient thermal protection. Among them, low thermal conductivity and high emissivity are considered to be ideal high-temperature thermal protection functions. Low thermal conductivity means that the coating itself has good thermal insulation properties and can effectively reduce heat transfer; high emissivity means that the coating can effectively release the absorbed heat quickly in the form of radiation, further improving its thermal protection effect. However, how to prepare high-temperature thermal protective coatings with these two functions, and how to ensure the stability and adhesion of the coating, are still challenges in practical applications.

[0004] Perovskite oxides usually exhibit good thermal stability, corrosion resistance, and antioxidant properties. Chromium-type perovskite is a relatively common type. The addition of chromium can enhance the stability of the crystal structure, allowing the material to maintain its crystal structure and functional properties under high temperature conditions. In particular, chromium may change the optical and electronic properties of perovskite, giving it a specific band structure and electronic transition characteristics, which is very beneficial for infrared radiation heat transfer. However, the infrared emissivity of chromium-based perovskite oxides reported so far is generally less than 0.9. Although doping with transition metals and rare earth metal elements can improve infrared emissivity, unstable intermediate phases are easily formed during the doping process, which reduces the thermal stability of the material and is not conducive to its application under high temperature conditions.

[0005] In recent years, high-entropy perovskite materials have gradually attracted widespread attention from scientists in the field of materials due to their unique combination principles and superior physical and chemical properties. Compared with traditional perovskites, high-entropy perovskites introduce five or more metal ions at their A and / or B positions, forming a highly mixed and statistically uniformly distributed complex configuration. This multi-element coexistence characteristic gives high-entropy perovskites a series of unique physical and chemical properties. Compared with traditional perovskite materials, high-entropy perovskites generally exhibit higher thermal stability and superior mechanical properties due to their high configuration entropy caused by the increase in the number of elements. In addition, its lattice distortion effect can increase phonon scattering, thereby inhibiting the propagation of phonons and reducing thermal conductivity. At the same time, based on the cocktail effect of high-entropy materials, the coexistence of multiple elements is expected to enhance the infrared emissivity of the material and bring higher radiation heat transfer efficiency. In addition, the entropy-assisted structural stabilization effect ensures that good protection performance can be maintained in high temperature environments.

[0006] Therefore, the use of high-entropy perovskite materials is an effective way to improve high-temperature thermal protection performance, but its preparation method, composition optimization, and compatibility with other materials still face challenges. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a functional high-temperature thermal protective coating with good performance, intrinsic low thermal conductivity and high emissivity.

[0008] In order to solve the above problems, the present invention discloses a functional high-temperature thermal protective coating with intrinsic low thermal conductivity and high emissivity, characterized in that: the working temperature of the high-temperature thermal protective coating is 800-1500°C, and the thermal conductivity is 1.2-1.6Wm - 1 K -1 , composed of the following raw materials in parts by weight: 10-15 parts of functional pigment, 20-25 parts of filler, 20-30 parts of high-temperature binder, 3-8 parts of additives and 15-25 parts of deionized water; the functional pigment is a high-entropy rare earth perovskite with a general chemical formula of RECrO3, wherein RE is five of the rare earth elements La, Pr, Ce, Nd, Sm, Gd, Y and Dy, and each rare earth element is in an equal molar ratio.

[0009] The functional pigment has a perovskite crystal structure, and its infrared emissivity in the 0.78 to 2.5 μm band is 0.84 to 0.90.

[0010] The functional pigment is prepared by the following method: using REOx powder and Cr2O3 powder with a metal element molar ratio of 1:1 as raw materials, ball milling and mixing, drying and grinding to obtain a mixture powder; the mixture powder is calcined at high temperature in an air atmosphere, cooled and ground to obtain; the REOx is Pr6O 11, La2O3, Ce2O3, Nd2O3, Sm2O3, Y2O3, Gd2O3, and Dy2O3.

[0011] The ball milling mixing conditions refer to using a planetary ball mill for wet ball milling, a ball milling speed of 300-500 r / min, a ball milling time of 5-12 hours, and a ball-to-material-water mass ratio of 2-5:1:3.

[0012] The high temperature calcination conditions refer to a calcination temperature of 900-1500°C, a heating rate of 3-10°C / min, and a calcination time of 2-6 hours; the cooling method is one of furnace cooling, air quenching cooling, and liquid nitrogen quenching cooling.

[0013] The filler is at least three of zirconium oxide, hafnium oxide, lapis lazuli, zircon, mullite, and clay, with a particle size of 20-100 nm and a specific surface area of ​​40-100 m 2 / g.

[0014] The high temperature binder refers to one or two of rare earth phosphate, silica sol and aluminum dihydrogen phosphate.

[0015] The auxiliary agent is a mixture of a leveling agent, a dispersant and a defoamer uniformly mixed in a mass ratio of 1:1:1 to 1:2:3; the leveling agent is one or two of Deqian 810 silicone leveling agent-polyether modified polysiloxane, AFCONA-3587-polyether modified silicone, and AFCONA-3085-polyether modified silicone; the dispersant is one or more of 5040 dispersant, LED-1 dispersant, S19 dispersant and sodium lignin sulfonate; the defoamer is one or two of polyether modified polydimethylsiloxane, polyoxyethylene polyoxypropanolamine ether and dimethyl silicone oil.

[0016] The method for preparing a functional high-temperature thermal protective coating with intrinsic low thermal conductivity and high emissivity as described above is characterized in that: the method refers to first weighing according to the ratio; then adding the functional pigment to the high-temperature binder, mechanically stirring for 10 to 15 minutes, and after stirring evenly, adding the filler, and mechanically stirring for 30 to 45 minutes to obtain a mixture A; adding deionized water to the mixture A, mechanically stirring for 10 to 15 minutes, and then adding the auxiliary agent, stirring evenly to obtain a mixture B; the mixture B is stirred for 1.5 to 3 hours using a planetary ball mill at a speed of 400 to 500 r / min.

[0017] A coating prepared using the high-temperature thermal protective coating as described above, characterized in that the coating has an emissivity of not less than 0.96 in the 0.78-2.5 μm band at room temperature.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] 1. The present invention adds rare earth-doped perovskite materials, which cause lattice distortion, destroy the original lattice vibration period, increase lattice vibration, and thus improve the light absorption performance and infrared radiation performance of the coating. At the same time, the structural stabilization effect driven by the entropy of the high entropy material increases the structural stability of the coating, greatly reducing the attenuation of infrared radiation performance under high temperature conditions, with an attenuation rate as low as 0.25%.

[0020] 2. The present invention increases the infrared emissivity of the coating by up to 0.96 by doping perovskite with rare earths, and the addition of rare earth elements reduces the intrinsic thermal conductivity of the coating. Rare earth metals have excellent thermal stability, and doping with multiple principal elements can also improve the thermal stability and thermal expansion coefficient of the material.

[0021] 3. The coating prepared by the coating of the present invention has a smooth, dense, no blistering, no cracking, and further improves the high temperature corrosion resistance. The coating prepared by the coating of the present invention is corroded in molten salt at 700°C for 240 hours. The molten salt is Na2SO4+K2SO4 with a mass ratio of 1:1. After the high temperature molten salt corrosion, the coating is smooth, dense, no blistering, and no cracking, indicating that the coating prepared by the coating has excellent high temperature molten salt corrosion resistance.

[0022] 4. The coating prepared by the coating of the present invention on the ceramic fiberboard was subjected to a thermal stability test in an air environment at 1300°C for 72 hours. The results showed that the coating prepared by the coating had excellent high temperature resistance.

[0023] 5. The coating prepared by the coating of the present invention can fully balance the heat exchange ratio of the heating surface of the high-temperature device and enhance the radiation heat exchange capacity, which is mainly manifested in reducing the heat accumulation on the aviation and aerospace surfaces and increasing the service life; enhancing the thermal utilization rate of high-temperature processing kilns, and playing a role in energy saving and efficiency improvement.

[0024] 6. The present invention has high production efficiency, does not require complicated heat treatment processes, and can realize large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.

[0026] Figure 1 For Example 1 of the present invention (La 0.2 Pr 0.2 Ce 0.2 Nd 0.2 Sm 0.2 )XRD pattern of CrO3.

[0027] Figure 2 Example 2 (La 0.2 Pr 0.2 Ce 0.2Nd 0.2 G 0.2 )XRD pattern of CrO3.

[0028] Figure 3 Example 2 (La 0.2 Pr 0.2 Ce 0.2 Nd 0.2 G 0.2 )Infrared radiation spectrum of CrO3 in the 0.78~2.5μm band.

[0029] Figure 4 Example 3 (La 0.2 Pr 0.2 Ce 0.2 Nd 0.2 Y 0.2 )XRD pattern of CrO3.

[0030] Figure 5 For Example 4 of the present invention (La 0.2 Pr 0.2 Ce 0.2 Nd 0.2 Dy 0.2 )XRD pattern of CrO3. DETAILED DESCRIPTION

[0031] A functional high-temperature thermal protective coating with intrinsic low thermal conductivity and high emissivity. The working temperature of the high-temperature thermal protective coating is 800~1500℃ and the thermal conductivity is 1.2~1.6Wm -1 K -1 , composed of the following raw materials in parts by weight (g); 10-15 parts of functional pigments, 20-25 parts of fillers, 20-30 parts of high-temperature binders, 3-8 parts of additives and 15-25 parts of deionized water.

[0032] The preparation method comprises the following steps: first, weighing according to the proportion; then, adding the functional pigment into the high-temperature binder, mechanically stirring for 10 to 15 minutes, and after stirring evenly, adding the filler, and mechanically stirring for 30 to 45 minutes to obtain a mixture A; adding deionized water into the mixture A, mechanically stirring for 10 to 15 minutes, and then adding the auxiliary agent, stirring evenly to obtain a mixture B; and stirring the mixture B for 1.5 to 3 hours at a speed of 400 to 500 r / min using a planetary ball mill to obtain the mixture.

[0033] Among them: the functional pigment is a high entropy rare earth perovskite, the chemical formula is RECrO3, where RE is five of the rare earth elements La, Pr, Ce, Nd, Sm, Gd, Y, and Dy, and each rare earth element is in an equal molar ratio. It has a perovskite crystal structure, and its infrared emissivity in the 0.78 ~ 2.5μm band is 0.84~0.90.

[0034] The functional pigment is prepared by the following method: using REOx powder and Cr2O3 powder with a metal element molar ratio of 1:1 as raw materials, REOx is Pr6O 11 , La2O3, Ce2O3, Nd2O3, Sm2O3, Y2O3, Gd2O3, and Dy2O3. The above raw materials are wet-milled in a planetary ball mill, the ball milling speed is 300-500 r / min, the ball milling time is 5-12 hours, and the mass ratio of ball material to water (g / g) is 2-5:1:3. Ball milling process: first ball mill for 1 hour, then pause for 10 minutes, then ball mill for 1 hour, pause for 10 minutes, and repeat the ball milling cycle. After ball milling and mixing, the mixture powder is dried and ground; the mixture powder is calcined at high temperature in an air atmosphere, the calcination temperature is 900-1500℃, the heating rate is 3-10℃ / min, and the calcination time is 2-6 hours. After calcination, it is cooled and ground by one of the methods of furnace cooling, air quenching cooling, and liquid nitrogen quenching cooling.

[0035] The filler is at least three of zirconium oxide, hafnium oxide, lapis lazuli, zircon, mullite, and clay, with a particle size of 20-100 nm and a specific surface area of ​​40-100 m 2 / g. The filler strongly enhances the light absorption, infrared radiation and thermal shock resistance of the coating.

[0036] The high temperature binder refers to one or two of rare earth phosphate, silica sol, and aluminum dihydrogen phosphate.

[0037] The additive is a mixture of leveling agent, dispersant and defoamer in a mass ratio (g / g) of 1:1:1 to 1:2:3. The leveling agent is one or two of Deqian 810 silicone leveling agent-polyether modified polysiloxane, AFCONA-3587-polyether modified silicone, AFCONA-3085-polyether modified silicone; the dispersant is one or more of 5040 dispersant, LED-1 dispersant, S19 dispersant and sodium lignin sulfonate; the defoamer is one or two of polyether modified polydimethylsiloxane, polyoxyethylene polyoxypropanolamine ether and dimethyl silicone oil.

[0038] A coating prepared by using the high-temperature thermal protective coating: the coating has an emissivity of not less than 0.96 in the 0.78-2.5 μm band at room temperature.

[0039] Example 1

[0040] (1) Functional pigments (La 0.2 Pr 0.2 Ce 0.2 Nd 0.2 Sm 0.2 Preparation of CrO3

[0041] Weigh La2O3 (1 mol), Pr6O 11 (1mol), Ce2O3 (1mol), Nd2O3 (1mol), Sm2O3 (1mol), Cr2O3 (5mol) powders; pour zirconia balls, raw materials and ultrapure water into a ball mill according to the mass ratio of ball material to water (g / g) of 2:1:3; place the ball mill on the ball mill station, first perform ball milling for 1 hour at a speed of 300r / min, then pause for 10min, which is a ball milling cycle, and then perform ball milling for another 1 hour at a speed of 300r / min after 10min, and ball milling for a total of 12 hours to obtain a mixed powder; then the mixed powder obtained after ball milling is dried and ground, and placed in a muffle furnace, heated to 900℃ in an air atmosphere (heating rate of 3℃ / min), calcined for 6 hours, and then air quenched and cooled to room temperature to obtain a single-phase (La 0.2 Pr 0.2 Ce 0.2 Nd 0.2 Sm 0.2 )CrO3 high entropy oxide powder, such as Figure 1 Its particle size is 20nm.

[0042] (2) Preparation of high temperature thermal protective coatings

[0043] Coating formula: 10 g (La 0.2 Pr 0.2 Ce 0.2 Nd 0.2 Sm 0.2 )CrO3, 20 g filler, 20 g high temperature binder, 3 g additive and 15 g deionized water.

[0044] The preparation method comprises the following steps: first, weighing according to the proportion; then, adding the functional pigment into the high-temperature binder, mechanically stirring for 10 to 15 minutes, adding the filler after stirring evenly, and mechanically stirring for 30 to 45 minutes to obtain a mixture A; adding deionized water into the mixture A, mechanically stirring for 10 to 15 minutes, then adding the auxiliary agent, and stirring evenly to obtain a mixture B; and stirring the mixture B with a planetary ball mill at a speed of 400 to 500 r / min for 1.5 to 3 hours to obtain the mixture.

[0045] Example 2

[0046] (1) Functional pigments (La 0.2 Pr 0.2 Ce 0.2 Nd 0.2 G 0.2 Preparation of CrO3

[0047] Weigh La2O3 (1 mol), Pr6O 11 (1mol), Ce2O3 (1mol), Nd2O3 (1mol), Gd2O3 (1mol), Cr2O3 (5mol) powders; pour zirconia balls, raw materials and ultrapure water into a ball mill according to the mass ratio of ball material to water (g / g) of 4:1:3; and place the ball mill on the ball mill station, first perform ball milling for 1 hour at a speed of 400r / min, then pause for 10min, which is a ball milling cycle, and after 10min, perform ball milling for another hour at a speed of 400r / min, and ball milling for a total of 8 hours to obtain a mixed powder; then the mixed powder obtained after ball milling is dried and ground, and placed in a muffle furnace, heated to 1000℃ in an air atmosphere (heating rate of 3℃ / min), calcined for 6 hours, and then air quenched and cooled to room temperature to obtain a single-phase (La 0.2 Pr 0.2 Ce 0.2 Nd 0.2 G 0.2 )CrO3 high entropy oxide powder, such as Figure 2 As shown, the infrared radiation spectrum of the powder in the 0.78~2.5μm band is as follows Figure 3 As shown, the particle size is 20 nm.

[0048] (2) Preparation of high temperature thermal protective coatings

[0049] Coating formula: 15 g (La 0.2 Pr 0.2 Ce 0.2 Nd 0.2 G 0.2 )CrO3, 25 g filler, 30 g high temperature binder, 8 g additive and 25 g deionized water.

[0050] The preparation method is the same as that of Example 1.

[0051] Example 3

[0052] (1) Functional pigments (La 0.2 Pr 0.2 Ce 0.2 Nd 0.2 Y 0.2 Preparation of CrO3

[0053] Weigh La2O3 (1 mol), Pr6O 11(1mol), Ce2O3 (1mol), Nd2O3 (1mol), Y2O3 (1mol), Cr2O3 (5mol) powders; pour zirconia balls, raw materials and ultrapure water into a ball mill according to the mass ratio of ball material to water (g / g) of 5:1:3; place the ball mill on the ball mill station, first perform ball milling for 1 hour at a speed of 400r / min, then pause for 10min, which is a ball milling cycle, and then perform ball milling for another 1 hour at a speed of 400r / min after 10min, and ball milling for a total of 8 hours to obtain a mixed powder; then the mixed powder obtained after ball milling is dried and ground, and placed in a muffle furnace, heated to 1300℃ in an air atmosphere (heating rate of 8℃ / min), calcined for 5 hours, and then air quenched and cooled to room temperature to obtain a single-phase (La 0.2 Pr 0.2 Ce 0.2 Nd 0.2 Y 0.2 )CrO3 high entropy oxide powder, such as Figure 4 Its particle size is 20nm.

[0054] (2) Preparation of high temperature thermal protective coatings

[0055] Coating formula: 12g (La 0.2 Pr 0.2 Ce 0.2 Nd 0.2 Y 0.2 )CrO3, 22 g filler, 22 g high temperature binder, 4 g additive and 18 g deionized water.

[0056] The preparation method is the same as that of Example 1.

[0057] Example 4

[0058] (1) Functional pigments (La 0.2 Pr 0.2 Ce 0.2 Nd 0.2 Dy 0.2 Preparation of CrO3

[0059] Weigh Pr6O 11(1mol), La2O3 (1mol), Ce2O3 (1mol), Nd2O3 (1mol), Dy2O3 (1mol), Cr2O3 (5mol) powders; pour zirconia balls, raw materials and ultrapure water into a ball mill according to the mass ratio of ball material to water (g / g) of 2:1:3; and place the ball mill on the ball mill station, first perform ball milling for 1 hour at a speed of 500r / min, then pause for 10min, which is a ball milling cycle, and after 10min, perform ball milling for another 1 hour at a speed of 500r / min, and ball mill for a total of 5 hours to obtain a mixed powder; then the mixed powder obtained after ball milling is dried and ground, and placed in a muffle furnace, heated to 1500℃ in an air atmosphere (heating rate of 10℃ / min), calcined for 2 hours, and then air quenched and cooled to room temperature to obtain a single-phase (La 0.2 Pr 0.2 Ce 0.2 Nd 0.2 Dy 0.2 )CrO3 high entropy oxide powder, such as Figure 5 Its particle size is 20nm.

[0060] (2) Preparation of high temperature thermal protective coatings

[0061] Coating formula: 18g (La 0.2 Pr 0.2 Ce 0.2 Nd 0.2 Dy 0.2 )CrO3, 24g filler, 26g high temperature binder, 7g additive and 20g deionized water.

[0062] The preparation method is the same as that of Example 1.

[0063] The high temperature thermal protective coating prepared in Examples 1 to 4 was sprayed on a substrate (nickel-based alloy 625), and then placed in a muffle furnace at 300°C for 1 hour and cooled with the furnace. The dry film thickness was 20 to 60 μm, and the dry film performance was tested.

[0064] 1. Reflection spectrum

[0065] The reflectance spectrum in the 0.78~2.5μm band was tested using an American Lambda950 UV-visible-near-infrared spectrophotometer (including a 150mm integrating sphere).

[0066] Test results: The emissivity of the ceramic material in the 0.78~2.5μm band is 0.84~0.90, and the emissivity of the coating in this band is not less than 0.96.

[0067] 2. Thermal conductivity

[0068] The heat capacity Cp was measured by differential scanning calorimetry (DSC) (Netzsch STA449F3, Germany). The thermal conductivity of the sample was obtained using the Kelemen formula, with reference to GB / T 10294-2008.

[0069] Test results: The thermal conductivity of the dry film is: 1.2~1.5Wm -1 K -1 , has a lower thermal conductivity, as shown in Table 1.

[0070] 3. Adhesion

[0071] The dry film adhesion is tested by the pull-off method, and the reference standard is ASTM D 4541 "Determination of the pull-off strength of coatings using a portable adhesion tester".

[0072] Test results: The dry film pull-off strength is greater than 5MPa, as shown in Table 1.

[0073] 4. Thermal shock resistance

[0074] The coating was placed in an air atmosphere in a box furnace, heated to 700°C at a heating rate of 5°C / min, kept warm for 30 minutes, taken out and water quenched, repeated 10 times, and the dry film surface was observed.

[0075] Test results: The dry film surface is intact, without peeling or cracks, as shown in Table 1.

[0076] 5. Dry film salt spray corrosion resistance test

[0077] Artificial atmosphere corrosion test-Salt spray test (NSS), test standard: GB / T 10125-2012.

[0078] Test results: After 1000 hours of salt spray test, the coating was intact and no corrosion occurred, as shown in Table 1.

[0079] Table 1 Characterization of coating properties prepared in Examples 1 to 4

[0080]

[0081] As can be seen from Table 1, the functional high-temperature thermal protective coating prepared by the present invention has good infrared radiation characteristics and low thermal conductivity, and the coating has excellent adhesion, thermal shock resistance and corrosion resistance.

[0082] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. All changes made within the scope of protection of the independent claims of the present invention are within the scope of protection of the present invention.

Claims

1. A functional high-temperature thermal protective coating with intrinsic low thermal conductivity and high emissivity, characterized in that: The working temperature of this high temperature thermal protection coating is 800~1500℃, and the thermal conductivity is 1.2~1.6Wm -1 K -1 , composed of the following raw materials in parts by weight: 10-15 parts of functional pigment, 20-25 parts of filler, 20-30 parts of high-temperature binder, 3-8 parts of auxiliary agent and 15-25 parts of deionized water; the functional pigment is high entropy rare earth perovskite, and the chemical formula is RECrO3, wherein RE is five of the rare earth elements La, Pr, Ce, Nd, Sm, Gd, Y, and Dy, and each rare earth element is in an equal molar ratio; the preparation method of the high-temperature thermal protective coating comprises the following steps: first, weighing according to the proportion; then adding the functional pigment to the high-temperature binder, mechanically stirring for 10 to 15 minutes, and after stirring evenly, adding the filler, and mechanically stirring for 30 to 45 minutes to obtain a mixture A; adding deionized water to the mixture A, mechanically stirring for 10 to 15 minutes, and then adding the auxiliary agent, stirring evenly to obtain a mixture B; the mixture B is stirred for 1.5 to 3 hours at a speed of 400 to 500 r / min using a planetary ball mill; the functional pigment has a perovskite crystal structure, which is 0.78 to The infrared radiation rate in the 2.5 μm band is 0.84-0.90; the functional pigment is prepared by the following method: REOx powder and Cr2O3 powder with a metal element molar ratio of 1:1 are used as raw materials for ball milling and mixing, and the mixture powder is obtained after drying and grinding; the mixture powder is calcined at high temperature in an air atmosphere, and then cooled and ground to obtain; the REOx is Pr6O 11 , La2O3, Ce2O3, Nd2O3, Sm2O3, Y2O3, Gd2O3, and Dy2O3; the ball milling mixing condition refers to wet ball milling using a planetary ball mill, the ball milling speed is 300-500 r / min, the ball milling time is 5-12 hours, and the mass ratio of ball material to water is 2-5:1:3; the high temperature calcination condition refers to a calcination temperature of 900-1500°C, a heating rate of 3-10°C / min, and a calcination time of 2-6 hours; the cooling method is one of furnace cooling, air quenching cooling, and liquid nitrogen quenching cooling; the high temperature binder refers to one or two of rare earth phosphate, silica sol, and aluminum dihydrogen phosphate.

2. A functional high-temperature thermal protective coating with intrinsic low thermal conductivity and high emissivity as claimed in claim 1, characterized in that: The filler is at least three of zirconium oxide, hafnium oxide, lapis lazuli, zircon, mullite, and clay, with a particle size of 20-100 nm and a specific surface area of ​​40-100 m 2 / g.

3. The functional high-temperature thermal protective coating with intrinsic low thermal conductivity and high emissivity according to claim 1, characterized in that: The auxiliary agent is a mixture of a leveling agent, a dispersant and a defoamer uniformly mixed in a mass ratio of 1:1:1 to 1:2:3; the leveling agent is one or two of Deqian 810 silicone leveling agent, AFCONA-3587, and AFCONA-3085; the dispersant is one or more of 5040 dispersant, LED-1 dispersant, S19 dispersant and sodium lignin sulfonate; the defoamer is one or two of polyether modified polydimethylsiloxane, polyoxyethylene polyoxypropanolamine ether and dimethyl silicone oil.

4. A coating prepared using the high-temperature thermal protective coating according to claim 1, characterized in that: The emissivity of the coating in the 0.78~2.5μm band at room temperature is not less than 0.96.

Citation Information

Patent Citations

  • Ultrathin high-temperature-resistant thermal-insulation paint

    CN104277653A

  • Chromic acid rare earth-based high-entropy ceramic conductive nanofiber as well as preparation method and application thereof

    CN116924798A